1982
DOI: 10.1029/jb087ib05p03831
|View full text |Cite
|
Sign up to set email alerts
|

Time relations and structural‐stratigraphic patterns in ophiolite accretion, west central Klamath Mountains, California

Abstract: New geochronological data and published structural and stratigraphic data show that two distinctly different ophiolitic assemblages formed in general proximity to one another at nearly the same time and were subsequently imbricated along a regional thrust zone. The Josephine ophiolite constitutes a complete oceanic crust and upper mantle sequence which lies within the western Jurassic belt of the Klamath province. Within the study area the Josephine ophiolite was formed by seafloor spreading at about 157 m.y. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 43 publications
7
96
0
Order By: Relevance
“…Garcia (1982) suggested that the BCA was metamorphosed pillow lava and dikes, and these units, along with the gabbros and peridotites in fault contact to the Table 1. west, made up a typical ophiolite sequence. U-Pb ages (Saleeby 1984) on zircon from the Rum Creek Gabbro to the west of the BCA range from 165 to 155 Ma, very similar to the ages determined on the Josephine Ophiolite to the south (Saleeby et al 1982) (see Table 1 & 2). Because of the temporal relations and juxtaposition of these mafic units, it is possible that the BCA may represent a fragment of oceanic crust equivalent to the Josephine Ophiolite.…”
Section: Geologic and Tectonic Settingsupporting
confidence: 53%
“…Garcia (1982) suggested that the BCA was metamorphosed pillow lava and dikes, and these units, along with the gabbros and peridotites in fault contact to the Table 1. west, made up a typical ophiolite sequence. U-Pb ages (Saleeby 1984) on zircon from the Rum Creek Gabbro to the west of the BCA range from 165 to 155 Ma, very similar to the ages determined on the Josephine Ophiolite to the south (Saleeby et al 1982) (see Table 1 & 2). Because of the temporal relations and juxtaposition of these mafic units, it is possible that the BCA may represent a fragment of oceanic crust equivalent to the Josephine Ophiolite.…”
Section: Geologic and Tectonic Settingsupporting
confidence: 53%
“…This age is concordant with a previous K/At hornblende age of 139*-4 Ma from a quartz monzonite located several km to the northwest [Hotz, 1971 ] The m'mimum westward displacement along the Orleans thrust is >40 km based on its outcrop pattern (Figures 1 and 2), and Jachens et al [1986] have estimated >110 km displacement based on geophysical data. Structural evidence for west or northwest directed thrusting of the older Klamath terranes over the Western Klamath terrane has been presented by many workers [Snoke, 1977;Harper, 1980Harper, , 1992Gray, 1985;Wyld, 1985;Jones, 1988;Harper, 1992 The numerous dikes and sills intruding the Josephine ophiolite and Galice Formation were previously considered to be pre-Nevadan because they are regionally metamorphosed and many are deformed [Harper, 1980;Saleeby et al, 1982;Harper and Wright, 1984;Wyld, 1985]. Deformation must have started by -150 Ma, however, because some of the dikes are intruded into small precleavage thrust faults in the Galice Formation [Harper, 1992] The relationship between foliation in the Grants Pass contact aureole and slaty cleavage in the Galice Formation needs further study, but the White Rock pluton farther north, which has a similar structural setting and age (141 Ma K/At biotite), has a dynamic contact aureole that overprints slaty cleavage [Kays, 1992].…”
Section: Grantsmentioning
confidence: 99%
“…f Menzies et al 1980;Beard and Day 1987;Edelman et al 1989;Saleeby et al 1989. early sea floor spreading in a forearc setting. A feature of the Josephine ophiolite that may be relevant to the Ingalls ophiolite is the presence of a "rift facies" (Saleeby et al 1982;Wyld and Wright 1988;Yule 1996) consisting of Josephine-age dike complexes, pillow lavas, and ophiolitic breccias intruded into and built on Late Triassic to Early Jurassic ophiolitic basement (Rattlesnake Creek terrane). This is best shown by the 164-Ma Devils Elbow Remnant of the Josephine ophiolite, which has a sheeted dike complex and pillow lavas overlain by the same hemipelagic and flysch sediments as the main Josephine body but is built on ophiolitic mé lange of Rattlesnake Creek terrane affinity (Wyld and Wright 1988 6C) and Cr-spinel compositions ( fig.…”
Section: Comparison Of the Ingalls Ophiolite And Other Jurassic Cordimentioning
confidence: 99%